A qualitative study of effective collaboration among nurse home visitors, healthcare providers and community support services in the United States. (20th September 2021) - Williams, Venice Ng; McManus, Beth M.; Brooks‐Russell, Ashley; Yost, Elly; Allison, Mandy A.; Olds, David L.; Tung, Gregory J.
Abstract: Collaboration across sectors is needed to improve community health, but little is known about collaborative activities among public health prevention programs. Using the Nurse‐Family Partnership® (NFP) home visiting program as context, this qualitative study aimed to describe effective collaboration among nurse home visitors, healthcare providers and community support services to serve families experiencing social and economic adversities. We used grounded theory to characterise collaboration with six purposively sampled NFP sites in the United States through in‐depth interviews. We interviewed 73 participants between 2017 and 2019: 50 NFP staff, 18 healthcare providers and 5 other service providers. Interviews were recorded, transcribed, validated and analysed in NVivo 11. Validation steps included inter‐coder consistency checks and expert review. Thematic memos were synthesised across sites. Most participants perceived collaboration to be important when serving families with complex needs, but substantial variation existed in the degree to which NFP nurses collaborate with providers dependent on provider type and community context. Factors that contributed to effective collaboration were relational in nature, including leadership commitment and provider champions, shared perceptions of trust, respect and value, and referral partnerships and outreach; organisational in terms of mission congruence between providers; and structural such as policy and system integration that facilitated data sharing and communication channels. These findings provide greater insights into effective cross‐sector collaboration and care coordination for families experiencing adversities. Collaboration across sectors to promote health among families experiencing adversities requires intentional efforts by all inter‐professional providers and continued commitment among all levels of leadership to coordinate services.